METAPHORICAL MOTIVATION IN ZOOLOGICAL PHRASEOLOGICAL UNITS - Fonseca, Heloisa Da Cunha [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2017)
This paper aims to discuss about metaphorical issues at the center of analysis of zoonyms phraseological units, created from animal names, in a contrastive study of the Brazilian Portuguese and the French of France. The paper mainly analyzes the issue of metaphorical motivation that has been widely discussed, since it seems to contradict the saussurian postulate of the arbitrariness of the sign. Furthermore, with the motivation it is possible to find generic bases for the metaphorical constructions and, in turn, the congruent metaphors of specific level that are closely related to the culture. Therefore, the theoretical constructs of the conceptual metaphor were used to achieve this work, especially those concerning Kovecses (2010), Lakoff and Johnson (1980) and Sardinha (2007), and also of cognitive semantics, observing Pamies (2011, 2012) and Mendoza's (2001) works.
Keywords: Phraseological unit; motivation; culture